2014
DOI: 10.1002/gps.4190
|View full text |Cite
|
Sign up to set email alerts
|

Community mental health teams for older people: variations in case mix and service receipt (II)

Abstract: Objectives: To determine the extent to which services provided to older people via community mental health teams (CMHTs) vary in duration, composition and intensity. In particular, to identify the degree to which differences between teams are due to casemix. Methods: Data were collected about the services provided to a random sample of patients from 15 CMHT caseloads, including contact with CMHT staff, other specialist mental health and social care services. The relationship between patients' needs and service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The authors, like us, note a weighting within CMHTsOP towards cases where the individual has a functional mental health problem, rather than dementia conditions. 284 Wilberforce et al 284 also note a huge variation of practices in CMHTsOP in England, similar to the findings of their literature review of 2008, which concluded that there was patchy evidence for CMHTsOP practices, compared with policy and practice guidance. 285 Our examination of every new case referred to 33 CMHTsOP suggests that only a very small part of work accepted by CMHTsOP focuses on supporting new cases of people with dementia and family carers at home.…”
Section: Recognition Of Dementia and Challenging Behaviour In Family mentioning
confidence: 70%
“…The authors, like us, note a weighting within CMHTsOP towards cases where the individual has a functional mental health problem, rather than dementia conditions. 284 Wilberforce et al 284 also note a huge variation of practices in CMHTsOP in England, similar to the findings of their literature review of 2008, which concluded that there was patchy evidence for CMHTsOP practices, compared with policy and practice guidance. 285 Our examination of every new case referred to 33 CMHTsOP suggests that only a very small part of work accepted by CMHTsOP focuses on supporting new cases of people with dementia and family carers at home.…”
Section: Recognition Of Dementia and Challenging Behaviour In Family mentioning
confidence: 70%
“…Importantly, CMHTs are able to directly access a range of personal and social care services, including specialist community care services for older people with dementia and other support needs. These are commonly delivered by separate organisations under contract to local commissioners, but CMHT practitioners may remain responsible for their coordination and reviewing successful delivery [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Support workers commonly work with clients with complex needs, requiring understanding and judgement relating to psychiatric risk and vulnerability (Warne & McAndrew , Wilberforce et al . ) and the locus of CMHT work in people's homes raises particular concerns about autonomous working and supervision (McCrae et al . ).…”
Section: Introductionmentioning
confidence: 99%